Cerâmica no Rio Grande do Sul: a trajetória de Tania Resmini - Berger, Rejane de Fátima Devicari (2011)
This research deals with the insertion of ceramics in graduation institutions and its legitimation as art through the Ceramics Salons occured in Rio Grande do sul State. Its consists in the study of of the plastic production of the artist Tania Resmini, approaching her artistic life path from her life history in a way to show informations and experiences stored during all her existence ally to aspects of a historical ceramics survey in the state. The methodology used is based on a qualitative approach in which the data were colected from narratives interviews and documental analysis. The process of data collecting happend in the artist Studio, located in Porto Alegre, RS. Two questions permeated the work development: the poetic production of the artist and its trajectory. With all this, the problematic proposed was the following: how Tania Resmini poetic is defined through the technique and form, in other words, how Tania works this important questions in her plastic production, in the context of ceramics in the south of Brazil.